Increased resistance to Nalidixic acid and Ciprofloxacin in Salmonella isolates from the Sub Himalayan region - Bhagra, Suruchi; Sood, Atal; Singh, DigVijay; Kanga, Anil (International Journal of Research in Medical Sciences, 2017)
Background: During the last two decades, increased resistance to nalidixic acid and ciprofloxacin has become a cause of global concern. The present study was undertaken to ascertain nalidixic acid and ciprofloxacin resistance in Salmonella isolates from our region. To know the true pattern of ciprofloxacin resistance by determining the minimum inhibitory concentration (MIC) through E-test. Methods: All the Salmonella isolates recovered from blood cultures were screened for nalidixic acid resistance using 30µg disc by the Kirby Bauer disc diffusion method. Ciprofloxacin susceptibility was done both by disc diffusion and MIC using CLSI breakpoints. Results: We analysed a total of 80 Salmonella isolates during the last three years. Salmonella enterica serovar Typhi was the predominant serovar in 51 (64.8%) isolates, followed by Salmonella enterica serovar Paratyphi A comprising 28 (36.2%) isolates. Amongst the total isolates 78 (97.5%) were nalidixic acid resistant. Of these 54 (67.5%) showed intermediate susceptibility and 9 (11.2%) were ciprofloxacin resistant by the disc diffusion technique. On the contrary 29 (36.2%) had decreased susceptibility to ciprofloxacin; while a larger number 38 (47.5%) were detected resistant to ciprofloxacin on determination of MIC by the E-test. Conclusions: Screening for nalidixic acid acts as a surrogate marker to detect ciprofloxacin resistance. However, the true pattern of ciprofloxacin resistance can be determined by calculating the MIC by the E-test.